Piercy, Hannah. 2023. Resistance to Love in Medieval English Romance: Negotiating Consent, Gender and Desire. Cambridge: D.S. Brewer. Pp. xi + 275. ISBN 9781843846727. - Wanchen Tai (SELIM)
Book review of Piercy, Hannah. 2023. Resistance to Love in Medieval English Romance: Negotiating Consent, Gender and Desire. Cambridge: D.S. Brewer. Pp. xi + 275. ISBN 9781843846727.